Analisis Nilai-Nilai Moral Dalam Buku Mahir Berbahasa Indonesia Smp Kelas Ix Terbitan Erlangga - Nur Fatihan Azzahraa; Azis .; Andi Sahtiani Jahri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the moral values contained in the book "Mahir Berbahasa Indonesia" for Junior High School Grade IX published by Erlangga and to analyze the extent to which the moral values in the book support the character formation of students in accordance with the goals of national education. The method used in this study is a type of qualitative research with the content analysis method, which involves identifying and grouping moral values contained in various types of learning texts. The results of the study show that the book contains moral values such as responsibility, hard work, empathy, solidarity, honesty, discipline, compliance with norms and laws, concern for the environment, self-confidence, and politeness. These values are presented in a context that is relevant to students' daily lives, making it easier for them to internalize and apply them in life. This study concludes that the book "Mahir Berbahasa Indonesia" for Junior High School Grade IX not only functions as a source of academic material, but also as an effective instrument in the character formation of students, supporting the goals of national education to create a generation of integrity and responsibility.